Filipino Language as an Auxiliary Medium of Instruction in Teaching Physics - Abdulrahman, Aljahir S.; Ali, Samirudin L.; Arenas, Joel C.; Unsi, Alibai L.; Sam, Solayha A. (Future Science / FSH-PH Publications, 2025)
This study investigated the effectiveness of using the Filipino language as an auxiliary medium of instruction in teaching Physics among Grade 10 students at Mindanao State University–Maguindanao Integrated Laboratory Science High School. The research employed an experimental pre-test and post-test design involving two groups: a control group taught through conventional English instruction and an experimental group taught with Filipino as a supplementary language during lessons on problem-solving and computations. Data were collected using validated and reliable test instruments and analyzed through mean scores, t-tests, and standard deviations. Findings revealed that the control group obtained a mean score of Fair, while the experimental group achieved a higher mean score of Good. Statistical analysis showed no significant difference between the two groups before instruction, but a significant difference after instruction. These results indicate that incorporating the Filipino language as an auxiliary medium significantly enhances students’ comprehension and performance in Physics, particularly in solving numerical and conceptual problems. The study concludes that bilingual instruction, where Filipino complements English, can serve as an effective pedagogical approach in Physics education. It aligns instruction with learners’ linguistic and cognitive capacities, promoting inclusivity, confidence, and academic achievement. The researchers recommend further integration of Filipino in science classrooms and a review of language policies to strengthen equitable and meaningful science learning.